2018
DOI: 10.1088/1361-6560/aad2b7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of imaging latency for real-time MRI-guided radiotherapy

Abstract: Hybrid MR-linac systems can use fast dynamic MR sequences for tumor tracking and adapt the radiation treatment in real-time. For this the imaging latency must be as short as possible. This work describes how different acquisition parameters influence this latency. First, the latency was measured for Cartesian readouts with phase encode orderings linear, reverse-linear, and high-low. Second, the latency was measured for radial readouts with linear and golden angle profile orderings. To reduce the latency, a spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 29 publications
1
51
0
Order By: Relevance
“…Lin‐PE was selected because of its widespread usage in clinical protocols and robustness to eddy current effects. Rnd‐PE was selected because it resembles the relatively large jumps in k‐space that are commonly seen in highly undersampled acquisitions for compressed sensing, low‐high profile ordering for low latency imaging or k − t sampling patterns for dynamic imaging. GA‐Rad was selected to represent non‐Cartesian with widespread utility in dynamic imaging .…”
Section: Methodsmentioning
confidence: 99%
“…Lin‐PE was selected because of its widespread usage in clinical protocols and robustness to eddy current effects. Rnd‐PE was selected because it resembles the relatively large jumps in k‐space that are commonly seen in highly undersampled acquisitions for compressed sensing, low‐high profile ordering for low latency imaging or k − t sampling patterns for dynamic imaging. GA‐Rad was selected to represent non‐Cartesian with widespread utility in dynamic imaging .…”
Section: Methodsmentioning
confidence: 99%
“…However, based on their results, template matching provides the best compromise between flexibility, speed and accuracy. In a study conducted by (Glitzner et al 2015b), the delay attributed to the multi-leaf collimator adaptation was shown to be a minor contributor to the overall feedback chain as compared to the impact of imaging components such as MRI acquisition and processing (Borman et al 2018), which therefore require mitigation strategies to predict tumour motion (Yun et al 2012, Seregni et al 2016, Krauss, Nill and Oelfke 2011.…”
Section: Intra-fraction Motion Managementmentioning
confidence: 99%
“…In the clinic, adaptive radiotherapy requires the MRI-Linac system to monitor the target tumor in real-time using continuously acquired MR images. 46 Thus, the latency for correcting geometric distortions, including GNL field characterization and undistorted image reconstruction, should be as short as possible. The superior efficiency of the proposed method enables the GNL field correction to be implemented with an acceptable latency.…”
Section: B Computational Complexitymentioning
confidence: 99%